The Influence of the Problem Based Learning Model Based on Subak Local Wisdom on Social Studies Learning Outcomes for Class V Elementary School Students - I Kadek Tediana Saputra; I Wayan Lasmawan; I Wayan Kertih (STKIP Taman Siswa Bima, 2024)
The purpose of this study was to analyze the effect of the PBL model based on local wisdom of Subak on social studies learning outcomes. This research method is experimental research, the type of research is a quasi-experiment with a nonequivalent control group design, the study population is all fifth grade students in the Letda Made Putra cluster. The sample was taken randomly with SD 2 Dangin Puri as a control class that was implemented without using the PBL model and the insertion of local wisdom of Subak and SD N 18 Dangin Puri as an experimental class by implementing the PBL model with the insertion of local wisdom of Subak. The technique of collecting learning outcome data with multiple choice tests. The results of the study, namely the results of the hypothesis test with one-way ANOVA obtained a significance value of 0.001 <0.05, which means that there is an effect of the PBL model based on local wisdom of Subak on the social studies learning outcomes of fifth grade elementary school students. There is an effect of the PBL model based on local wisdom of Subak on the social studies learning outcomes of fifth grade elementary school students, it is recommended that further research be able to measure variables other than learning outcomes with the insertion of other local wisdom.